Anti-crease Finishing of Cotton Fabrics Based on Crosslinking of Cellulose with Oxidized Sucrose. Issue 7 (3rd July 2022) - Lou, Jiangfei; Yuan, Jiugang; Wang, Qiang; Xu, Jin; Fan, Xuerong
ABSTRACT: In anti-crease finishing, the hydrophilicity of cotton fabric treated with traditional anti-crease finishing agents such as dimethylol dihydroxy ethylene urea (DMDHEU), 1, 2, 3, 4, -butanetetracarboxylic acid (BTCA), citric acid (CA) was reduced significantly. Oxidized sucrose (OS) was prepared by partial oxidation with sodium periodate. The OS was used as a hydrophilic cross-linking agent instead of conventional anti-crease agents. The chemical structure of the OS characterized by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance, and aldehyde groups were found in the OS. The effects of OS mass concentration, catalyst mass concentration, pH, curing temperature and curing time on the crease recovery angle (CRA), whiteness index (WI) and strong retention rate (TS %) of fabrics were studied. The optimal finishing process was an OS mass concentration of 150 g/L, a catalyst mass concentration of 20 g/L, pH 3 and curing for 3 min at160°C. The OS-treated cotton fabrics could obtain a maximum CRA of 245°, WI of 82.8 and TS% of 65%. Compared with DMDHEU, glutaraldehyde, BTCA and CA finishing fabrics, the OS finishing fabric had a shorter wetting time of 5.01 s and a higher water retention.